PREBIOTICS, INULIN AND BABY FOODS - S.V. Bel'mer; T.V. Gasilina ("Paediatrician" Publishers LLC, 2010)
Prebiotics play significant role in life support of microorganisms of human gastrointestinal tract, and normal functional state of intestinal biocenosis is sufficient condition for human health. Intestinal microbiocenosis is a component of regulation of proteins and lipids metabolism, vitamins synthesis, detoxication process in intestine, etc. prebiotics include a number of disaccharides (lactulose), oligosaccharides and polysaccharides (inulin, cellulose, etc.). Fructose polymer - inulin - provides growth of bifido- and lactobacteria, improves metabolism and has immunomodulating activity. Formation of intestinal micro biocenosis in infant is provided by prebiotics of breast milk. Further state of micro biocenosis, which is necessary for growth and development of child, is determined by adequate intake of prebiotics from fruits, vegetables and cereals. It is reasonable to use special baby foods fortified with prebiotics (for example, inulin).Key words: prebiotics, intestinal microflora, inulin.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):121-125)